PENGUJIAN MODEL KESUKSESAN SISTEM INFORMASI DELONE DAN MCLEAN PADA SISTEM APLIKASI PEMERIKSAAN (SIAP) DI BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN PROVINSI SULAWESI UTARA - Wara, Lidya Stefany; Kalangi, Lintje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2021)
This study aims to test the DeLone and McLean information system success model on a mandatory and relatively new system, namely the Ssitem Aplikasi Pemeriksaan (SiAP) at Badan Pemeriksa Keuangan Republik Indonesia (BPK RI) Perwakilan Provinsi Sulawesi Utara. This research was conducted on auditors at BPK who used the Sistem Aplikasi Pemeriksaan (SiAP).The research method used is a quantitative research method with structural equation model (SEM). Data were obtained through questionnaires distributed to 60 auditors in BPK RI Perwakilan Provinsi Sulawesi Utara. The data analysis tool used in this study was the Partial Least Square Structural Equation Model (PLS-SEM), with the help of SmartPLS software.The results show that some of the DeLone and McLean models can be used to assess the success of the Sistem Aplikasi Pemeriksaan. The net benefit variable is affected by user satisfaction but not by use. User satisfaction is only affected by the quality of information. While the use variable is affected by the system quality and service quality.